Intimate partner violence as a determinant factor for spontaneous abortion during pregnancy: an unmatched case–control study - Hailu, Helen Teweldebrhan; Mekonnen, Wubegzier; Gufue, Zenawi Hagos; Weldegebriel, Selamawit Gebreyohannes; Dessalegn, Berhe (Frontiers in Public Health, 2023)
Background: Intimate partner violence affects a significant portion of women worldwide throughout their lifetimes. Ethiopia lacks data that policymakers could utilize to develop context-specific policies for handling intimate partner violence during pregnancy. Objectives: To identify the determinants of spontaneous abortion among women survivors of intimate partner violence during pregnancy in Adigrat General Hospital, Northern Ethiopia, in 2020. Methods: A facility-based, case-control study design was employed to recruit 371 women (124 cases and 247 controls) attending maternal health services in Adigrat General Hospital, Northern Ethiopia, from March 13 to June 12, 2020. Cases and controls were selected using a consecutive sampling technique. A multivariable binary logistic regression model was carried out to identify potential factors, and a p-value of 0.05 was used to declare statistical significance. Results: The proportion of any form of intimate partner violence during pregnancy among cases and controls was 53.23% and 34.82%, respectively. Any form of intimate partner violence (AOR = 3.66; 95% CI 1.69–7.95), physical intimate partner violence (AOR = 3.06; 95% CI 1.69–7.95), and an interpregnancy interval of 24 months (AOR = 4.46; 95% CI 1.65–12.07) were the independent determinants of spontaneous abortion among survivors. Conclusions: Spontaneous abortion was significantly associated with exposure to any form of intimate partner violence, including physical intimate partner violence, and a shorter inter-pregnancy interval.